2012
DOI: 10.26509/frbc-ec-201214
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Libor in Consumer Mortgages

Abstract: Many adjustable rate mortgages in the United States are indexed to Libor. While the accuracy of this rate has recently been called into question, another issue affecting U.S. borrowers has become evident since the onset of the financial crisis. Specifically, many U.S. consumers with Libor-based loans may have been hit with substantially higher payments when their loans reset during the financial crisis than if those loans had been tied to a Treasury rate. We investigate several alternative reference rates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The market for U.S. treasuries is likely the most liquid in the world, even under financial duress. Moreover, Treasury constant maturity rates were heavily used as a reference rate for ARMs prior to the popularization of LIBOR, and in fact is still referenced by many ARMs today (Schweitzer and Venkatu 2012). The possibility of replacement using a combination of several rates has also been discussed.…”
Section: Repair and Reform Or Replacementioning
confidence: 99%
“…The market for U.S. treasuries is likely the most liquid in the world, even under financial duress. Moreover, Treasury constant maturity rates were heavily used as a reference rate for ARMs prior to the popularization of LIBOR, and in fact is still referenced by many ARMs today (Schweitzer and Venkatu 2012). The possibility of replacement using a combination of several rates has also been discussed.…”
Section: Repair and Reform Or Replacementioning
confidence: 99%
“…SeeMcCauley and Seth (1992), who describe how an asymmetry in the eurodollar reserve requirement's application to US chartered banks versus foreign banks' US branches at times gave foreign banks a funding advantage over US banks in their US lending.11Schweitzer and Venkatu (2009) showed that LIBOR replaced domestic interest rate benchmarks in most prime ARMs and in all subprime ARMs in Ohio in the 2000s.…”
mentioning
confidence: 99%